Evidence for the Decay B-s(0)->(DsDs(*))-D-(*) and a Measurement of Delta Gamma(CP)(s)/Gamma(s) - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Safronov, G.; et al. (Amer Physical Soc, 2009)
We search for the semi-inclusive process B-s(0)->(DsDs(*))-D-(*) using 2.8 fb(-1) of pp collisions at s=1.96 TeV recorded by the D0 detector operating at the Fermilab Tevatron Collider. We observe 26.6 +/- 8.4 signal events with a significance above background of 3.2 standard deviations yielding a branching ratio of B(B-s(0)->(DsDs(*))-D-(*))=0.035 +/- 0.010(stat.)+/- 0.011(syst.). Under certain theoretical assumptions, these double-charm final states saturate CP-even eigenstates in the B-s(0) decays resulting in a width difference of Delta Gamma(CP)(s)/Gamma(s)=0.072 +/- 0.021(stat.)+/- 0.022(syst.).